Tinjauan Estetika Tari Piriang Jorong Limau Sundai Pasir Talang Solok Selatan - Desfiarni . (Fakultas Bahasa dan Seni UNP, 2012)
This article aims to explain about the aesthetic value in performance structure of traditional piriang dance from Jorong Limau Sundai Pasir Talang, Kabupaten Solok Selatan. This dance is played especially by female dancers. This research is quantitative research which applies descriptive method. The object of this research is the performance structure of traditional piriang dance from Jorong Limau Sundai Pasir Talang Kabupaten Solok Selatan. The key instrument of this research is the researcher herself. The data are colected by using direct observation, interview, literature study and documentation. Furthermore, the data are analyzed by using ethnography method. Based on result of this research, piriang dance has traditional aesthetics from local culture values of Jorong Limau society. The aesthetic value of piriang dance can be found in motion structure, costume, floor design, music design, dance technique, and expression of the female dancers who are 45 until 48 years old. The aesthetic value of piriang dance from Jorong Limau is related to culture value which becomes the basic of life to Jorong Limau Sundai society. Keywords: Piriang dance Jorong Limau Sundai, aesthetic value, dance performance